Safety net adjustments and review, July-September 1994 : Commonwealth Government submissions and exhibits (Australian Govt. Pub. Service, 1995)
The Government's 1994 submission to the Australian Industrial Relations Commission in relation to wage fixing guidelines, industrial awards and the safety net.